Financial Hardship in Adult Survivors of Childhood Cancer in the Era After Implementation of the Affordable Care Act: A Report From the Childhood Cancer Survivor Study. Issue 5 (10th February 2023) - Nathan, Paul C.; Huang, I-Chan; Chen, Yan; Henderson, Tara O.; Park, Elyse R.; Kirchhoff, Anne C.; Robison, Leslie L.; Krull, Kevin; Leisenring, Wendy; Armstrong, Gregory T.; Conti, Rena M.; Yasui, Yutaka; et al.
Abstract : PURPOSE: To estimate the prevalence of financial hardship among adult survivors of childhood cancer compared with siblings and identify sociodemographic, cancer diagnosis, and treatment correlates of hardship among survivors in the era after implementation of the Affordable Care Act. METHODS: A total of 3, 555 long-term (≥ 5 years) survivors of childhood cancer and 956 siblings who completed a survey administered in 2017-2019 were identified from the Childhood Cancer Survivor Study. Financial hardship was measured by 21 survey items derived from US national surveys that had been previously cognitively tested and fielded. Principal component analysis (PCA) identified domains of hardship. Multiple linear regression examined the association of standardized domain scores (ie, scores divided by standard deviation) with cancer and treatment history and sociodemographic characteristics among survivors. RESULTS: Survivors were more likely than siblings to report hardship in ≥ 1 item (63.4% v 53.7%, P < .001). They were more likely to report being sent to debt collection (29.9% v 22.3%), problems paying medical bills (20.7% v 12.8%), foregoing needed medical care (14.1% v 7.8%), and worry/stress about paying their rent/mortgage (33.6% v 23.2%) or having enough money to buy nutritious meals (26.8% v 15.5%); all P < .001. Survivors reported greater hardship than siblings in all three domains identified by principal component analysis: behavioral hardship (mean standardized domain score 0.51 v 0.35), material hardship/financial sacrifices (0.64 v 0.46), and psychological hardship (0.69 v 0.44), all P < .001. Sociodemographic (eg, <college education, without private insurance) and treatment factors (eg, received ≥ 250 mg/m 2 anthracycline chemotherapy, or chest radiation) were statistically significantly associated with increased hardship. CONCLUSION: Survivors of childhood cancer were more likely to experience financial hardship than siblings. Correlates of hardship can inform survivorship care guidelines and intervention strategies.